2019
DOI: 10.1590/1982-0194201900073
|View full text |Cite
|
Sign up to set email alerts
|

Pessoas vivendo com HIV/Aids no cárcere: regularidade no uso da terapia antirretroviral

Abstract: Resumo Objetivo Analisar os desafios relacionados à regularidade no uso da terapia antirretroviral pelas pessoas vivendo com HIV privadas de liberdade. Métodos Trata-se de um estudo exploratório, com abordagem quantitativa, realizado em seis unidades prisionais de dois municípios paulistas. A coleta de dados ocorreu no período de agosto a novembro de 2015, mediante entrevistas, com apoio de instrumento específico. Os dados foram analisados a partir de técnicas descritivas, análise univariada (testes de ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
(12 reference statements)
0
4
0
4
Order By: Relevance
“…When observing the intermediate determinants of health related to living conditions and behavioral and biopsychosocial factors, we identified that AIDS was a risk factor for unfavorable treatment outcomes in both states. The evolution of HIV to AIDS today denotes weaknesses in health care systems, especially regarding the timely detection of cases of HIV infection and the provision and monitoring of the regular use of antiretroviral therapy (ART) in the prison context 32 . Thus, it is worth highlighting the need to improve access to diagnosis and monitoring of HIV/AIDS cases, not as a privilege or out of compassion, but as a constitutional right 33 , since individuals in deprivation of liberty are under the State's tutelage.…”
Section: Discussionmentioning
confidence: 99%
“…When observing the intermediate determinants of health related to living conditions and behavioral and biopsychosocial factors, we identified that AIDS was a risk factor for unfavorable treatment outcomes in both states. The evolution of HIV to AIDS today denotes weaknesses in health care systems, especially regarding the timely detection of cases of HIV infection and the provision and monitoring of the regular use of antiretroviral therapy (ART) in the prison context 32 . Thus, it is worth highlighting the need to improve access to diagnosis and monitoring of HIV/AIDS cases, not as a privilege or out of compassion, but as a constitutional right 33 , since individuals in deprivation of liberty are under the State's tutelage.…”
Section: Discussionmentioning
confidence: 99%
“…For confirmed cases of TB-HIV coinfection, about 60% refer the provision of ART, being incipient in the prison context, since it must be offered to all people living with HIV (21) . In South Africa, short-term interventions involving the training of nurses in TB diagnosis and treatment, as well as the increase in number of facilities with decentralized HIV services have been recommended to allow the prescription and administration of ART by nurses (10) .…”
Section: Discussionmentioning
confidence: 99%
“…Health teams in the prison environment also face difficulties that can compromise the integration of HIV health actions and services, among which the need for military police escort for any displacement of PDL for HIV follow-up, with availability of the resource from the optimization and selection of legal and health nature priority demands (21) .…”
Section: Discussionmentioning
confidence: 99%
“…No intuito de cumprir com as metas, criou-se o modelo epidemiológico cascata do cuidado contínuo, o qual tem o controle do monitoramento da epidemia e do diagnóstico precoce, para proporcionar a oferta medicamentosa, supressão viral e a criação de vínculo entre usuário e equipe, que se faz necessária nesta trajetória (WILTON et al, 2019). Diante dessa realidade em que o Brasil ainda vive é essencial que sejam desenvolvidas e realizadas estratégias para o fortalecimento do acesso e adesão a TARV (RAVANHOLI et al, 2019). Com isso, buscou-se identificar os principais motivos da não adesão a TARV.…”
Section: Introductionunclassified